Analisis Penggunaan DeepL Write AI Sebagai Teknologi Pendukung dalam Perbaikan Penulisan Bahasa Asing di Kalangan Mahasiswa - Refina Shafa Awalia; Abelia Ferrita Nuhaa; Missel Azuainun Putbyhah; Oktalis Oktalis (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
In the era of society 5.0, advances in digital technology have developed rapidly in the lives of the Indonesian people. One of the current digital technologies is artificial intelligence or better known as Artificial Intelligence (AI). DeepL is one of the popular online translator websites used because it utilizes Artificial Intelligence (AI) in deciphering writing. DeepL has become a very useful tool for individuals and organizations in overcoming language barriers. This study aims to analyze the Deepl Write AI platform that is often used by students for foreign language improvement in writing assignments and scientific papers. The research method using descriptive explanatory qualitative type was chosen to convey facts by providing explanations from the data obtained. The results of this study show that DeepL which uses AI contributes to improving students' writing skills and confidence.